2017
DOI: 10.1007/s10840-017-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of acute inefficacy and the radiofrequency energy time required for cavotricuspid isthmus-dependent atrial flutter ablation

Abstract: Tricuspid regurgitation is associated with less acute efficacy in CTI-AFL ablation. Prior CTI ablation, COPD, use of an irrigated catheter, and advanced age are independent predictors for needing less RF energy time to achieve a complete bidirectional CTI block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Sometimes, prophylactic cavotricuspid isthmus ablation is needed to combine with PV isolation, which may be considered for patients with COPD. However, the recurrence of arrhythmia after first ablation is higher in this type of patients and most of them needed to be performed a second ablation [ 13 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, prophylactic cavotricuspid isthmus ablation is needed to combine with PV isolation, which may be considered for patients with COPD. However, the recurrence of arrhythmia after first ablation is higher in this type of patients and most of them needed to be performed a second ablation [ 13 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed marked heterogeneity in CTI architecture, and morphological variations such as trabeculae or recesses and structural anomalies can affect procedural and long‐term outcomes 25–27 . Data from contact‐force sensing catheters suggest that site‐specific inconsistencies in isthmus tissue contact may be responsible for procedural failure 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed marked heterogeneity in CTI architecture, and morphological variations such as trabeculae or recesses and structural anomalies can affect procedural and long-term outcomes. [25][26][27] Data from contact-force sensing catheters suggest that site-specific inconsistencies in isthmus tissue contact may be responsible for procedural failure. 28 Our study is the first to make use of precise LI characteristics and derived/associated LI lesion parameters to describe the heterogeneity encountered when ablating the CTI.…”
Section: Characteristics Of Ablation Lesions Along the Ctimentioning
confidence: 99%
“…The main objective of ablation is the termination and non-reinduction of clinical arrhythmia ( 2 , 45 , 66 , 70 71 ). However, it is not uncommon for the patient to present in sinus rhythm, or for more than one arrhythmia to be induced.…”
Section: Specific Arrhythmia Typesmentioning
confidence: 99%